Halal Tourism Industry for the Improvement of Micro Economy in Gorontalo: Potential, Opportunity, and Challenge - Perdana, Dian Adi; Tomayahu , Moh Hidayat; Kaaba , Titin S (JURNAL PENELITIAN, 2022)
This research analyzes and examines the prospects, potentials, and obstacles to the development of halal tourism to improve a micro-economy in Gorontalo. This research is field research with descriptive qualitative analysis. The data source in this study is primary data obtained from the central and additional respondents who are assisted with secondary data from various literature in previous studies and essential archives in the field of tourism management. The techniques of taking the subject of this research are interview, observation, and documentation. The results of this study show that tourism marketing strategies throughout Gorontalo Province need to run better and by the wishes of tourist visitors because many obstacles still need to be resolved. SWOT analysis is carried out using the IFE (Internal Factor Evaluation) matrix, which describes the strengths and weaknesses of the company and the EFE (External Factor Evaluation) matrix, which describes the company's opportunity and threat factors, and the IE (Internal External) matrix which shows the position of the tourism industry currently halal in Gorontalo. The strengths and threats are more significant than the weaknesses, opportunities, and other factors. Therefore, it is a profitable position and must be watched out for, the manager has good strength, and there are threats from external or competitors for halal tourism in other provinces in Indonesia so that the manager can utilize the internal forces of the tours they have to the maximum and management parties also need to implement strategies that can minimize external threats, by making policies, forming an implementing team and a supervisory team to support tourism in Gorontalo Province to become visitorfriendly halal tourism.